Hubungan Perilaku Ibu Dan Dukungan Keluarga DenganKelengkapan Imunisasi Dasar Pada Masa Pandemi - Rizki Aprillia, Adinda; Elisabeth Isti Daryati; Rosa Nora Lina (PT. Pubsains Nur Cendekia, 2023)
Background: Immunization is an effective way to boost the immune system and prevent infection of diseases that can be prevented by immunization (PD3I). Immunization services in Indonesia have declined by 87% in 2020 due to the COVID-19 pandemic. Purpose: This study aims to analyze the relationship between mother’s behavior and family support with basic immunization completeness during the pandemic period in Primary Healthcare Service (PKM) Kampung Manggis. Methods: Quantitative research with correlation design and cross-sectional approach methods. The population in this study was a mother who had a child aged 9-18 months in PKM Kampung Manggis with a total of 77 mothers. The sample was calculated using the Slovin formula, and the sample amounted to 72 mothers. Results: The statistical test used was the Chi-Square test, which obtained the result of the existence of a relationship between mother’s behavior (p = 0.009) and there was no relationship between family support (p= 0.183) with basic immunization completeness. Conclusion: COVID-19 affects the mother’s behavior in supplementing immunization for the child. Recommendations for future researchers to add health-supporting energy variables to basic immunization completeness.